2022
DOI: 10.1002/ecs2.4257
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perceptions of rural and urban communities towards small protected areas: Insights from Ghana

Abstract: Conservationists recognize that protected areas (PAs) have limited prospects without the involvement and support of local people. People inherently express positive perceptions to nature and support for wildlife conservation.Yet, people in rural and urban communities may differ in their knowledge and perceptions of benefits and costs of nearby small-size PAs, which induce a vital impact on the effectiveness of PAs and conservation goal achievements. We investigated local people's knowledge, perceptions, and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…It was established that there was a strong positive and significant (p < 0.05) association between local people's perceptions of wildlife conservation and tourism (r = 0.72). This indicated that the more local people perceived the positive of wildlife conservation, the higher their perceptions of wildlife tourism and vice versa (Afriyie, Opare, & Hejcmanová, 2022).…”
Section: Mean 41mentioning
confidence: 98%
“…It was established that there was a strong positive and significant (p < 0.05) association between local people's perceptions of wildlife conservation and tourism (r = 0.72). This indicated that the more local people perceived the positive of wildlife conservation, the higher their perceptions of wildlife tourism and vice versa (Afriyie, Opare, & Hejcmanová, 2022).…”
Section: Mean 41mentioning
confidence: 98%
“…However, the reality is that this understanding often neglects their rights to oversee, manage, and utilize resources, while also suffering from a lack of necessary trust [109,110]. This triggers dissatisfaction and resistance from community residents towards NPs, leading to resentment against conservation policies [111]. In some areas, this may even lead to violent conflicts between community residents and the park rangers or guards of NPs [32,101,104].…”
Section: Livelihood Concerns For Residents Of National Park Communitiesmentioning
confidence: 99%
“…Other results, however, have shown that those at the lower end of society and the disadvantaged are more vulnerable to climate change and environmental events daily and therefore have a strong and sometimes greater pro-environmental view than those at the higher end of society [12,[24][25][26][27]. While economic position is indeed important to environmental perceptions, a host of studies have also focused on other sociodemographic characteristics such as gender [28,29], race [12], and location [30].…”
Section: Literature Reviewmentioning
confidence: 99%